Product development and accelerated storage studies of dehydrated pineapple (Ananas comosus Linn. mer.) - Bernad, Mary Carolyn Q. (1986)
The purpose of this study was to evaluate three pre-drying treatments to prevent browning of dehydrated pineapple, namely water blanching, steam-blanching, and sulfiting. The fruits used for the study weighed 2.50 to 3.35 kg measuring 8 to 10 inches in length (excluding the crown) and 16 to 17 inches in circumference. The pineapple had a 52.4% edible portion on the average. The best pretreatment was found to be sulfiting which was evaluated as being moderately plump, yellow, chewy, with a characteristic pineapple flavor, and a general acceptability rating of dislike slightly (3.9); the steam blanched sample, moderately plump, dull yellow, tough, with a slight pineapple flavor and rated between dislike slightly and neither like nor dislike (4.4). Accelerated storage studies (100% RH, 30°C) were done on the sulfited sample, with the control (candied dehydrated pineapple) for comparison. The objective tests results during the 6-day storage period showed the following ranges: moisture content of the sulfited sample (14.5-24%); control (13-16%; water activity (.649-0.705)for the sulfitd sample and .581-.665 for the control; Browning index : 0.46 - 0.75 um and 0.99-1.10 respectively; Titrable acidity : sample (1.60-1.80%) and control (1.85-2.38%); pH for the sample (4.33-4.40) and control (3.60-4.20); Soluble solids: sample (55.0-66.0%) and control (55.8-79.2%); and yeast and mold count: sample (3 colonies on day 4 and 196 on day 6) and control (0 throughout the 6 days). The critical moisture content of the sulfited dehydrated pineapple determined to be 21.2% on the 4th day of storage, the point at which the product was organoleptically and microbiologically unacceptable.